PELATIHAN MEMBATIK TEKNIK SHIBORI SEBAGAI PONDASI UTAMA DALAM MEMBANGUN BISNIS KREATIF DI DESA KERSIK - Puspita, Desi; Andrean, Andrean; Fourqoniah, Finnah; Fikry Aransyah, Muhammad; Bharata, Wira (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Shibori Technique Batik Making Training as the Main Foundation in Building a Creative Business in Kersik Village. This research aims to examine the potential for creative business development in Kersik Village through batik training using the Shibori technique. It is hoped that this training method will provide sufficient knowledge and skills for the local community to produce batik products with unique Shibori characteristics. In this way, it is hoped that the people of Kersik Village can utilize this expertise as a basis for opening sustainable creative businesses, increasing local economic income, and ultimately, supporting holistic village development. This research encourages the adoption of traditional technology in a modern business context, stimulates local economic growth, and celebrates the cultural heritage of Kersik Village through the art of batik using the Shibori technique.